Respuesta :
Answer:
[tex]10x-6[/tex]
Step-by-step explanation:
[tex]f(x) = 5x+2x\\g(x)=3x-6[/tex]
[tex](f+g)(x)\\f(x)+g(x)[/tex]
[tex]5x+2x+3x-6\\10x-6[/tex]
The value of (f+g)(x) is 10x - 6
Addition of two functional equation -
We are taking into consideration the following two functions f(x) and g(x). The sum of these functions can be written f(x) + g(x) or as (f + g)(x). . The sum of the two functions is the sum of the two polynomials. Or in other words, the sum of any two functions gives us the addition of the terms present inside the function.
How to find the addition (f+g)(x) given in the question ?
Given functions, f(x) = 5x + 2x
and g(x) = 3x - 6
Sum of the two functions -
∴ (f+g)(x) = f(x) + g(x) = 5x + 2x + 3x - 6 = 10x - 6
Therefore (f+g)(x) = 10x - 6
To learn more about addition of two functional equation, refer -
https://brainly.com/question/16442867
#SPJ2